2013
DOI: 10.1186/1477-7827-11-106
|View full text |Cite
|
Sign up to set email alerts
|

Castration-induced testosterone deficiency increases fasting glucose associated with hepatic and extra-hepatic insulin resistance in adult male rats

Abstract: BackgroundTestosterone deficiency is associated with insulin resistance. However, how testosterone deficiency affects insulin actions remains unclear. The aim of this study was to investigate the influence of castration-induced testosterone deficiency on the metabolic kinetics of glucose and to evaluate the hepatic and extra-hepatic insulin sensitivity, in advanced-age male Sprague–Dawley (SD) rats.MethodsTen-week-old male SD rats were randomly divided into three groups: (1) a control group (n = 10) in which t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 27 publications
0
36
0
Order By: Relevance
“…Ten weeks after castration, the β-cell mass was reduced to 30% of that observed in control rats and an excessive rise in glucose levels was observed 30 min after glucose injection [103]. This type of glucose intolerance reflects impairment of β-cell function [166], and castration has been shown to decrease insulin levels following a glucose load in male rats [162]. Testosterone also increases insulin expression [169] and suppresses the β-cell death induced by streptozotocin in male rats [170,171].…”
Section: Insulin Secretion By Pancreatic β-Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten weeks after castration, the β-cell mass was reduced to 30% of that observed in control rats and an excessive rise in glucose levels was observed 30 min after glucose injection [103]. This type of glucose intolerance reflects impairment of β-cell function [166], and castration has been shown to decrease insulin levels following a glucose load in male rats [162]. Testosterone also increases insulin expression [169] and suppresses the β-cell death induced by streptozotocin in male rats [170,171].…”
Section: Insulin Secretion By Pancreatic β-Cellsmentioning
confidence: 99%
“…Non-obese castrated rats show exacerbated hepatic and extra-hepatic (including muscle) insulin resistance, which increases the fasting glucose level [162]. Obese AR-KO or castrated mice showed a decreased [95,125,140] or unchanged [111,126] insulin sensitivity.…”
Section: Insulin Sensitivitymentioning
confidence: 99%
“…Castration studies have been conflicted showing decreased weight [35], improved glucose tolerance [36], increased insulin sensitivity [37], and improved triglycerides [38] even with increased fat mass, with other studies showing that castration impairs glucose tolerance and insulin resistance [39•]. AR-KO mice also show increased adiposity [40] and improved insulin sensitivity consistent with a deleterious role for androgens in adipose tissue [41].…”
Section: Animal Models Identify Sex Differences In Adipose Tissue Biomentioning
confidence: 99%
“…15) In addition, several studies have suggested that hypogonadism induces abnormal hepatic regulation of glucose homeostasis. 10,14,15,24) Hence, unlike in ARKO mice, surgical castration may induce obesity mainly via involvement of hepatic gluconeogenesis rather than adipocyte lipid metabolism. However, more information is needed about the profiles of genes which are highly regulated by androgens as well as HSL in Cast mice.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in male rats, castration induces insulin resistance with fasting hyperglycemia or hepatic steatosis. 14,15) In male mice, castration increases plasma adiponectin levels and induces glucose uptake into white adipose tissue (WAT). [16][17][18] In terms of fat accumulation in WAT, Floryk et al 19) reported that soon after surgical castration (i.e., within 14 d), WAT mass is reduced in male mice, even though androgen-depressive therapies clearly induce obesity in human clinical cases.…”
mentioning
confidence: 99%